Foot screening and customized health education program for patients with diabetic peripheral neuropathy: A nurse-led, real-world observational study - Shuhong Liu; Hexiao Ding; Dandan Li; Fen Lu; Gumei Luo; Yujin He; Hui Li; Xiuhong Zeng; Kaixin Li; Dong-E Gong; Xiling Hu; Yanming Chen; et al. (International Journal of Nursing Studies Advances)
Background: Research has shown that DPN affects 50 % of individuals with diabetes and, in severe cases, can lead to amputation or death. Interventions led by doctors for DPN have demonstrated limited effectiveness in delaying its onset and progression. Nevertheless, there is an increasing recognition of the significance of nurse-led screening and health education in the early detection and slowing down of DPN. Method: The present study conducted a retrospective analysis of medical records of 10,191 diabetic patients from 2019 to 2023, who also regularly attended outpatient clinics. Patients with incomplete medical data, transfers, critical conditions or death, existing foot ulcers or amputations, bedridden or uncooperative individuals (5,470 individuals) were excluded, and a total of 4,721 individuals were selected for analysis. The screening and intervention components of the FSCHE program were all led by nurses. A total of 2022 participants received foot screening and customized health education (FSCHE) program, while 2699 participants recevied regular care. The primary outcome is on determining the prevalence rate of DPN among all the included diabetic patients. The data was collected through experimental tests and nurse-led foot screening. Prevalence rates were reported as the number of cases per 1000 individuals. Odds Ratios were calculated to approximate Risk Ratios to determine the effectiveness of the FSCHE program. Results: The prevalence of DPN in diabetic patients who received the FSCHE program decreased from 557 cases per 1000 individuals in 2019 to 199 cases per 1000 individuals in 2023. The hospitalization duration decreased from 11.2 days to 7.59 days. The risk of DPN in diabetic patients participating in the FSCHE program was 0.741 times higher than that of regular diabetes care (RR [95 % CI]: 0.741 [0.654, 0.840], p < 0.001). The DPN-related risk factors showed promising control results as well. Conclusions: In this observational study conducted among Chinese patients with diabetes, it was found that the nurse-led FSCHE program effectively manages DPN and its associated risk factors. These results highlight the importance of employing objective screening tools to detect DPN at an early stage, as well as the significance of nurse-led interventions in promoting healthy behaviors and preventing the development and progression of DPN.